Waist Circumference for Central Obesity Detection from the Pre-Elderly Stage to the Elderly Stage in Indonesia: A Longitudinal Study - Yunita, Jasrida; Sartika, Ratu Ayu Dewi (Pakistan Journal of Nutrition, 2019)
Background and Objective: Waist circumference is an alternative to determine nutritional status (central obesity) and is an early detector of chronic diseases. This study was conducted to determine whether changes in waist circumference could detect central obesity from the pre-elderly stage to the elderly stage in individuals in Indonesia. Materials and Methods: The study followed a longitudinal design using secondary data from the Indonesian Family Life Survey from 2007 and 2014. The population of this study was comprised pre-elderly (53-59 years old) individuals who were observed until they reached their elderly years (60-66 years old). The eligible sample comprised 1324 respondents. Results: There was an increase in central obesity prevalence from 42.1% (pre-elderly) to 47.2% (elderly). The prevalence of obesity was 50.4% (pre-elderly-women) to 68.8% (elderly-women); the prevalence of obesity was 33.2% (pre-elderly-men) to 23.9% (elderly-men). Over 7 years, there was an increase of 2.42 cm in the mean waist circumference (men = 1.33 cm, women = 3.43 cm). Changes in body weight, fiber consumption, number of chronic diseases and physical activity were associated with changes in waist circumference (p<0.05; R2 = 0.64). Conclusion: Changes in waist circumference (central obesity) in the elderly are caused by changes in weight, fiber consumption, number of chronic diseases and physical activity beginning at the pre-elderly stage. Normal weight, high fiber consumption, absence of chronic diseases and physical activity for more than 30 min a day should be maintained beginning in the pre-elderly stage to ensure a normal waist circumference in the elderly stage.